Antiplatelet treatment in unstable angina: aspirin, clopidogrel, glycoprotein IIb/IIIa antagonist, or all three?. Issue 1 (1st July 2002) - Harding, S A; Boon, N A; Flapan, A D
Abstract : Evidence on the role of antiplatelet agents in patients with non-ST elevation acute coronary syndrome is reviewed, and a strategy for their use in unstable angina is presented